The level of satisfaction of internal stakeholders on the implementation of the relevance of the MBKM-based learning process at the Faculty of Animal Science, Universitas PGRI Kanjuruhan Malang - Aju Tjatur Nugroho Krisnaningsih; Tri Ida Wahyu Kustyorini; Dimas Pratidina Puriastuti; Waluyo Edi Susanto Susanto; Brihandhono Brihandhono (Journal of Education Technology and Inovation, 2022)
This study aims to determine the extent to which the level of satisfaction of the academic community as internal stakeholders on the relevance of the MBKM-based learning process at the Faculty of Animal Husbandry, Unikama. The method used in this research is a survey. The variables measured are the level of satisfaction of the academic community regarding the improvement of Soft-skills and hard skills obtained after participating in the MBKM-based learning process, breadth of the learning experience, effectiveness in dealing with the world of work, and application of methods. case method learning in student lectures. The research data were processed and analyzed based on the percentage of alternative answers to questionnaires and presented descriptively. The results showed that the level of respondents' satisfaction with the improvement of Soft-skills and hard skills obtained after participating in the MBKM Program in Competency/Skills Development as a provision after graduation, breadth of the learning experience, effectiveness in dealing with the world of work, application of the case method learning method in student lectures. produces a very good response. It can be concluded that the implementation of the MBKM-based learning process at the Unikama Faculty of Animal Science provides a very good level of internal stakeholder satisfaction